Temperature dependence of crystal growth behavior of AlN on Ni–Al using electromagnetic levitation and computer vision technique. (January 2023) - Adachi, Masayoshi; Hamaya, Sonoko; Morikawa, Daisuke; Pierce, Benjamin G.; Karimi, Ahmad M.; Yamagata, Yuji; Tsuda, Kenji; French, Roger H.; Fukuyama, Hiroyuki
Abstract: Bulk AlN single crystal has a great demand as a substrate material for AlGaN-based optical and electronic devices such as deep ultraviolet light-emitting diodes and high-power transistors. We have previously proposed a novel solution-growth method using Ni–Al solution with an in-situ observation system for solution growth of AlN crystal using electromagnetic levitation. In this paper, to investigate AlN formation behavior on 40 mol%Al–Ni droplets, two precisely synchronized high-speed cameras from the horizontal and vertical directions were installed. AlN formation behavior was evaluated quantitatively using computer vision image processing techniques. Based on the results, we demonstrated the growth of thick AlN film at 2030 K for 1 h. A 3.8-μm-thick c-axis oriented AlN film successfully formed on the droplet, and the film was also oriented in-plane. The + c-direction AlN film grew towards the droplet center from the surface by reacting dissolved nitrogen and Al atoms. Highlights: The authors have developed an original solution growth method using Ni–Al melt. AlN growth on Ni–Al droplet was investigated precisely by our original system. AlN formation behavior was evaluated using computer vision image processing. A 3.8-μm-thick c-axis and in-plane oriented AlN film formed on the Ni–Al droplet.